Medicaid and Nursing Home Choice: Why Do Duals End Up in Low-Quality Facilities?. (September 2020) - Sharma, Hari; Perraillon, Marcelo Coca; Werner, Rachel M.; Grabowski, David C.; Konetzka, R. Tamara
We provide empirical evidence on the relative importance of specific observable factors that can explain why individuals enrolled in both Medicare and Medicaid (duals) are concentrated in lower quality nursing homes, relative to those not on Medicaid. Descriptive results show that duals are 9.7 percentage points more likely than nonduals to be admitted to a low-quality (1-2 stars) nursing home. Using the Blinder–Oaxaca decomposition approach in a multivariate framework, we find that 35.4% of the difference in admission to low-quality nursing homes can be explained by differences in the distribution of observable characteristics. Differences in education and distance to high-quality nursing homes are important drivers, as are health status and race. Our findings highlight the need for creative policy solutions targeting the modifiable factors to reduce the disparity.